Dynamically tunable long-range coupling enabled by bound state in the continuum - Haijun Tang; Can Huang; Yuhan Wang; Xiong Jiang; Ruiheng Jin; Yue Cui; Shumin Xiao; Qinghai Song (Light: Science & Applications)
Abstract Formation and dynamic control of strong coupling among cavities are essential to realize advanced functional photonic and quantum circuits. Especially for cavities at distant distance or arbitrary locations. Conventional approaches suffer from short coupling distance, poor controllability, fixed locations and low wavelength uniformity, significantly restricting the scalability of photonic and quantum networks. Here, we exploit the intrinsic advantages of optical bound state in the continuum (BIC) and demonstrate an all-in-one solution for long-range coupled cavities. BIC metasurface can support a series of finite-sized quasi-BIC microlasers at arbitrary locations. The quasi-BICs microlasers have the same wavelength and are inherently connected through BIC metasurface. Consequently, the coupling distances in experiment increase significantly from subwavelength to tens of micrometers. Such long-range interaction in BIC metasurface enables scaling to two-dimensional architectures and ultrafast control of internal laser actions, e.g., non-Hermitian zero-mode lasing. This research shall facilitate the advancement of scalable and reconfigurable photonic networks.